DEVELOPMENT OF COOPERATIVE-BASED STUDENT WORKSHEETS ON KALOR MATERIALS AND TRANSFER CLASS VII SMP/MTs - Sulastri, Susi; Af'idah, Noer (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
The background of this research is based on observations at MTs Qamarul Huda Bagu, it was found that science learning is still teacher-centered, while students prefer practical activities and discussions. The purpose of this study was to develop student team achievement division cooperative-based worksheets on heat and transfer materials for class VII in SMP/MTs and feasibility developing cooperative student achievement division on heat and transfer materials for class VII in SMP/MTs based on the validity of the developed worksheets.This study uses the ADDIE development model, with the Analysis, Design, Development, Implementation, and Evaluation stages. However, in this study the implementation stage was not carried out because it was hindered by pandemic Covid-19. The product resulting from the research on the development of cooperative worksheets based on student achievement division on heat material and its transfer is very valid based on the validation results from two lecturers including a media expert lecturer and a material expert lecturer as well as a science teacher at SMP/MTs with an average score of 3, 27.